Patient Falls in Labor and Delivery. Issue 1 (June 2015) - Baker, Brenda; Dupree, Jeanette
<x xml:space="preserve">Abstract</x> Poster Presentation Purpose for the Program At an urban academic medical center with approximately 2200 births per year, 10 falls occurred in labor and delivery (L&D) unit in a 12‐month period. None of the patients who fell was categorized, as high risk for falling, which led the nurses to ask if the current risk scale for falls was useful in the perinatal population. The hospital‐wide falls screening tool had little application in the perinatal population because the tool was validated in the geriatric population. A review of the literature revealed little evidence as most studies excluded perinatal patients from their validation work. The purpose of this project was to create an obstetric specific falls prevention program and screening tool to identify women at risk of falling and decrease the number of falls in the L&D unit. Proposed Change To create a population specific falls prevention program and screening tool to identify pregnant women at risk of falling and decrease the incidence of falls in the perinatal population. Implementation, Outcomes, and Evaluation A review of literature was conducted using CINAHL and PubMed. Search terms included falls and pregnancy. Nine publications related to falls in pregnancy met search the criteria. Findings from this review indicated history of previous fall, visual disturbances, sedentary life style, and edema in feet and ankles during pregnancy as most predictive of risk of falling. Along with the review of literature, an in‐depth analysis of each fall event was completed. This work lead to development of a clinical practice guideline, Falls Prevention in Labor & Delivery, and a population‐specific screening tool built in the Electronic Medical Record. Staff education and monthly chart audits were conducted to monitor adherence to the tool and to provide feedback related to use of the screening tool. In 2008, 10 falls were reported. After the implementation of the obstetric falls program, two falls were reported in 2013. Implications for Nursing Practice A continual decline in patient falls in L&D has occurred since implementation of multiple initiatives, including a population specific screening tool. Future plans include validation of the screening tool.